Population-Based Estimates of the Prevalence of Uterine Sarcoma Among Patients With Leiomyomata Undergoing Surgical Treatment. Issue 6 (June 2015) - Mao, Jialin; Pfeifer, Samantha; Zheng, Xi Emily; Schlegel, Peter; Sedrakyan, Art
<x xml:space="preserve">Abstract</x> ABSTRACT Uterine leiomyoma (ULM) is common among women in the United States and is associated with abnormal uterine bleeding as well as pelvic pressure and pain. The annual diagnosis rate for ULM ranges from 2.0 to 12.8 per 1000 reproductive-age women. Standard surgical management for symptomatic patients includes open and laparoscopic hysterectomy, uterine artery embolization, myolysis, and magnetic resonance–guided focused ultrasound. Electric morcellation has been used by surgeons during laparoscopic and robotic-assisted hysterectomies and myomectomies as a less invasive alternative to open surgery. Concern that morcellation may spread occult sarcoma tissue led the US Food and Drug Administration (FDA) in April 2014 to issue a statement discouraging the use of this technique. Based on a literature search, the FDA reported that 1 in 352 women undergoing surgery for presumed benign ULM have occult uterine sarcoma. A study published in July 2014 reported similar results: 1 in 368 women undergoing morcellation had uterine cancer. The estimates in this study, however, were limited by the lack of pathologic confirmation and by the selective participation of hospitals. Moreover, the literature estimates used by the FDA may overestimate risk because of referral and reporting bias. The aim of this study was to determine the population-based estimates of the prevalence of uterine sarcoma and the risks of major complications after open surgery. Surveillance, Epidemiology, and End Results data were used to identify uterine sarcoma cases recorded between 2008 and 2011 from all California registries. Population denominators were obtained by selecting patients from the California State Inpatient Database and the State Ambulatory Surgery Database who underwent hysterectomy or myomectomy between 2008 and 2011. Two estimates were calculated to provide a reasonable range for prevalence of uterine sarcoma. The first was obtained by including patients as the population denominator who received a diagnosis of ULM and who underwent hysterectomy or myomectomy; this overestimates the prevalence of uterine sarcoma. The second included in the denominator all patients who underwent hysterectomy or myomectomy (any diagnosis); this may underestimate prevalence of uterine sarcoma. Data were stratified by race and age. Prevalence estimates for sarcoma were highly dependent on age; the lowest prevalence was found among women younger than 50 years (0.08%–0.13%) and the highest among women older than 60 years (0.36%–1.53%). Using conservative prevalence estimates (0.13%–1.53%), 1 in 769 women younger than 50 years had sarcomas, whereas 1 in 65 women older than 60 years had sarcomas. There was a higher prevalence among white and black women than among women of other races. Stratified by 3 age groups (>50, 50–59, and >59 years), open surgery was associated with in-hospital mortality rates of 0.01%, 0.02%, and 0.33%, and the risks of acute myocardial infarction were 0.32%, 0.26%, and 0.92%, respectively. In summary, stratified analyses show a 10-fold higher prevalence of uterine sarcoma among women older than 60 years than those women younger than 50 years. The risk of uterine cancer with morcellation should be weighed against the possible increased risk of death and major complications following open surgery without morcellation.